Conservative Management of Endometrial Cancer Permitting Subsequent Triplet Pregnancy: A Case Report - Karaltı, Mehmet Onur; Önoğlu, Ahmet Seçkin; Tınar, Şivekar; Kurt, Sefa; Karacaer, Muharrem; Atlı, Özgür (Gynecology Obstetrics & Reproductive Medicine, 2006)
Grade 1 endometrial adenocarcinoma was diagnosed by endometrial biopsy after suspicious ultrosonographic f indings in 28-y ear-old inf ertile women. After high dose progesterone therapy follow up endometrial biopsy was normal.The patient subsequently underwent ovultion induction cycles and triplet pregnancy had achieved.In caref ully chosed cases, conservative management of inf ertile patients with endometrial cancer may be a v iable option permitting subsequent successful pregnancies.